SUBTLE LANGUAGE OF PALEMBANG (BEBASO): LOCAL LANGUAGE PRESERVATION OF EXTINCTION THROUGH PREPARING DICTIONARY - HOUTMAN, HOUTMAN; AGUSTINA, JUAIDAH
The activity about the research of Subtle Language of Palembang (Bebaso) is done as an effort to preserve local language which is in the middle of extention. The language is already rare in used. Nowadays, the people of Palembang use a local language which is called daily Palembang language that stands out because it is dominated by Malay speech. As it is known that this article is started from withering and concern over the disappearance of the narrative and the use of this bebaso Palembang in public daily life communication. Language preservation as one of strategic steps in the preservation of language, should always be encouraged. One which can be done is by preparing subtle Palembang langauge (bebaso) which until now is still not arranged well. This step will be used as a basis to pursue the implementation of subtle language of Palembang as one of the local contents in teaching in schools that has a powerful function as a form of exploration of one of the cultural richness of South Sumatra to be proud.